SELECTION FACTORS INFLUENCED CHOOSING COURSE IN THE HIGHER ACADEMIC INSTITUTION - A REVIEW - M.H. Norhidayah; R. Nursabila (Journal of Islamic, Social, Economics and Development, 2023)
Lately, there has been rapid growth in the supply of new courses in institutions of higher learning (IPTA) and private (IPTS). This trend witnessed an increasing share of competition in the admission of students to institutions of higher learning. Education at all levels is the primary catalyst of quality human capital for the benefit of mankind. This study aims to give an overview of the factors that encourage students to choose certain courses in higher education institutions. Factors to be addressed in terms of interest, disclosure in the early stages, parental influence, peer influence, and career promotion. This study can be helped to the department or higher study institutions in increasing the number of students and the quality of study